Terahertz time-domain spectroscopy studies of nanocomposites - Xia, Huanxin (2016)
Terahertz time-domain spectroscopy (THz-TDS) is a powerful tool which has been used to probe the low-energy excitations in metals and semiconductors. The THz transmission signal is sensitive to the presence of free carriers, phonons, excitons, and the interplay among these degrees of freedom. The most remarkable advantage of THz-TDS is the simultaneous acquisition of the amplitude and phase of the THz pulses, which allows us to obtain the complex permittivity (or equivalently, complex optical conductivity) without using the Kramers-Kronig relationship. The ability to obtain the real and imaginary parts of the optical conductivity severely restricts the physical models that can explain the data. In this thesis, after introducing the experimental setup and data analysis procedure, the main experimental results are presented.